Aplicação da fibra óptica em sistemas FTTX - Carvalho, Priscila [UNESP] (2015)
The evolution in telecommunications with the extensive use of optical fiber following the technological expansion and data transmission demand becomes a necessity today. In this paper a literature review with technical concepts, feasibility of projects and applications in data collection with comparisons and highlights of the current situation of this advance is presented. The benefits of using optical fiber and the advantages of FTTH architecture are identified, as well as concrete and devised projects that make this theme reality and future prospects in the continuity of speed increase and allowed broadcasts growth